The Effectiveness of Animated Videos and Quizizz on Learning Outcomes in Natural and Social Sciences Among Fourth-Grade Elementary Students - Reva Reva; Abdul Rahman; Nuraini Nuraini; Nashrullah Nashrullah; Dyah Aini Purbarani (Papanda Publisher, 2026)
This study investigates the effectiveness of animated videos and Quizizz on student learning outcomes in Natural and Social Sciences (IPAS) among fourth-grade elementary students. A quasi-experimental design with nonequivalent control group pretest-posttest was employed, involving 40 students at SD Negeri 8 Mamboro divided into experimental (n=20) and control (n=20) groups. The experimental group received instruction through animated videos and Quizizz, while the control group continued with conventional methods over three weeks. Data were collected using validated achievement tests (Cronbach's α = 0.767) and analyzed through Mann-Whitney U and Wilcoxon Signed-Rank tests. Results revealed significant differences between groups, with the experimental group achieving superior posttest performance (M = 76.75, SD = 11.154) compared to controls (M = 65.00, SD = 15.728), confirmed by Mann-Whitney U test (U = 104.000, p = 0.009). Normalized gain analysis demonstrated moderate effectiveness for the experimental group (N-Gain = 0.4876) versus low effectiveness for controls (N-Gain = 0.2688). Completion rates improved substantially from 5% to 60% in the experimental group, compared to 10% to 25% in controls. These findings support cognitive theory of multimedia learning and self-determination theory, demonstrating that integrated implementation of animated videos and Quizizz significantly enhances elementary science learning outcomes through dual-channel information processing and gamified assessment that sustains motivation and engagement.